Suicide and 'hidden suicide': a comparison of rates in selected countries. (August 2020) - Snowdon, John
Objective: To review rates of suicide and 'hidden suicide' in New Zealand (NZ), Australia, Ireland and Spain. Method: Using estimated population figures and online cause-of-death data from four countries, rates of suicide and 'hidden suicide' in 2014–2016 were calculated and compared. Results: Age patterns and rates of suicide and 'hidden suicide' differ between these countries. The male suicide rate progressively rises across the age range in Spain but becomes lower in late life in Ireland. The male patterns in NZ and Australia are bimodal; male and female rates decrease in late life, with NZ lower than Australia. Māori age patterns are downward-sloping. Suicide rates of young Māori considerably exceed those of young non-Māori in NZ. Conclusions: The NZ youth suicide peaks are attributable to high rates of Māori youth suicide. Rates of 'hidden suicide' are relatively low in the four countries.